Economic Impact of CO2 Emissions and Carbon Tax in Electric Vehicle Society in Toyohashi City in Japan - Yuzuru Miyata; Hiroyuki Shibusawa; Tomoaki Fujii (European Regional Science Association (ERSA), 2015)
In this paper, we explore the economic impact of promotion and realization of an electric vehicle society (EVS) in Toyohashi City in Japan. More concretely, this paper emphasizes a computable general equilibrium (CGE) modeling approach to evaluate the following issues: economic impacts of subsidies for promotion of an EVS, economic impacts of carbon tax for reducing CO2, industrial structure change towards an EVS, and modal shift occurring towards an EVS. Our simulation results demonstrate that after applying 5 ~ 25% up subsidies to five industries including electric vehicle (EV) manufacturing, EV transport, solar power, cogeneration and other transport, the total industrial output and city GDP increase. A large growth rate is found in industries where subsidies are introduced, but non-ferrous metal industry also grows without subsidies due a repercussion effect. Moreover, it is interesting that decreasing proportions are found in oil and coal product, mining, heat supply and gasoline vehicle (GV) transport industries. However the total CO2 emission in Toyohashi City is increased being interpreted as a rebound effect. All the commodity prices decrease since subsidies are given to some industries. Hence Toyohashi Cityfs economy shows a direction where the demand for conventional vehicles and energy use are decreased, conversely, the demand for EVs and renewable energy are increased illustrating a different life style from the current one. Regarding CO2 emissions, we introduced a carbon tax of 1,000 yen/t-CO2 for industries except the five industries mentioned above. As a result the total CO2 emission is decreased and the equivalent variation shows a positive value as compared with the base case. Thus introducing 5 ~ 25% subsidies and the carbon tax can really represent a realistic alternative society to EVS in Toyohashi City.
Keywords: Q00; Q01; Q50; Q51; Q53; Q55; 330; CGE model; electric vehicle; carbon tax; solar power; Toyohashi City